Principle of Islamic Law and Moral Dilemmas of Religious Organisation's Involvement in Mining - Fanani, Ahwan; Budiman, Mamdukh (Universitas Muhammadiyah Surakarta, 2024)
This paper aims to bridge the moral dilemmas that arise from government policies granting mining concessions to religious organisations and the role of refligious organisations as social controls on the policy and practice of mining against the moral of law. Moral dilemmas revolve around the risks of involvement, the formation of new oligarchies, economic equity, economic actor diversification, and increased bargaining power for natural resource access. This exploratory study employs the Islamic legal maxim and maqȃṣid shari'a as ethical references. The data, such as legal acts and government regulations, were obtained from the literature. The findings indicate that the real problems of mining and other natural resource exploitation are mismanagement and environmental degradation. Islamic ethics based on the Islamic legal maxim and maqȃṣid shari'a can be used as guidance for civil society organisations to address natural exploitation. However, biocapacity deficit and mismanagement due to overlapping rules and authorities in Indonesia are major obstacles to applying Islamic ethics. This paper suggests that hifẓ bi'ȃh may act as a benchmark for state resource management policies to guide private rights in natural resource management to promote renewable energy industry capacity and ecosystem balance.